Efeitos da indução de estresse mental na variabilidade da frequência cardíaca em atletas de Badminton - (:unkn) unknown (Universidade Brasil, 2021)
The objective of the study was to analyze the effects of mental stress induction on heart rate variability in Badminton athletes. The study is direct, descriptive, experimental, cross-sectional and quantitative, carried out with the 15 highest ranked in the State of Piauí, by the Brazilian Confederation of Badminton, in January 2019. The sample consisted of 8 women and 7 men, with the average age of 19 years-old (+2.85), where the majority belonged to the main category (53.33%), participated in international competitions (66.66%) in all modalities (80%). The athletes were submitted to a previous anamnesis, measurement of blood pressure (BP), evaluation of HRV and Computerized Stroop Test. The procedures started with the placement of the Polar® H10 transmitter for the evaluation of the HRV in the participants, who went through a 5 min adaptation moment, when their BP was measured. After another 5 minutes of rest and BP measurement again, the Stroop Test of TESTIPACS® was then applied and the HRV evaluation was completed. For the analysis of HRV, the intervals were fragmented into 1 min, so that possible changes in the signals could be observed and only the resting moment and application of the Stroop Test were considered. All procedures were approved by the Ethics and Research Committee of Centro Universitário Uninovafapi (PI) (#3147702). It can be observed that the stressful stimulus promoted an increase in the mean HR and a decrease in the mean of the RR intervals, which suggests a physiological response that reflects the activation of the cardiac autonomic function, also perceived in the reduction of the SDNN, RMSSD, NN50 and pNN50 components. The high stress index during the time of application of the Stroop Test corroborates the values of the increased SNS index. The components of the frequency domain showed an increase in LF and LF/HF and maintenance of HF, while in the results of the Poincaré graph, the values of SD1 and SD2 reduced and the SD2/SD1 ratio increased. In the correlation analyses, it is possible to notice that the performance regarding the reaction time of the Stroop test is directly proportional to the components RMSSD, NN50, pNN50 and to the PNS index, while the stress index is inversely proportional. The other components did not show statistical significance. It is possible to verify that the Stroop Test was able to generate physiological changes with important responses in HRV, but further studies are needed on the stressful effect on athletes, as they are frequently subjected to both physical and mental stress, and that this frequency can lead to long-term cardiac overload.
Keywords: Estresse psicológico; Atletas; Teste de Stroop; Exercício físico; Sistema nervoso autônomo; CS